2016
DOI: 10.1364/oe.24.008028
|View full text |Cite
|
Sign up to set email alerts
|

Avalanche of stimulated forward scattering in high harmonic generation

Abstract: © 2016 [Optical Society of America]. One print or electronic copy may be made for personal use only. Systematic reproduction and distribution, duplication of any material in this paper for a fee or for commercial purposes, or modifications of the content of this paper are prohibited.Optical amplifiers in all ranges of the electromagnetic spectrum exhibit an essential characteristic, namely the input signal during the propagation in the amplifier medium is multiplied by the avalanche effect of the stimulated em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

11
36
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(47 citation statements)
references
References 29 publications
(58 reference statements)
11
36
0
Order By: Relevance
“…Note that Fig. 3 nicely 155 reproduces the shape of the IR electric field as it was already 156 observed in [14]. The particular cases shown in Fig.…”
supporting
confidence: 65%
See 4 more Smart Citations
“…Note that Fig. 3 nicely 155 reproduces the shape of the IR electric field as it was already 156 observed in [14]. The particular cases shown in Fig.…”
supporting
confidence: 65%
“…In particular, 26 we showed that forward scattering can be largely enhanced 27 when an XUV pulse is optimally synchronized with the IR 28 pulse [11]. This theoretical prediction was soon corroborated 29 by experiments [12] and a further detailed comparison between 30 the theory and the experimental measurements showed good 31 qualitative agreement [14]. Strong-field-mediated intrapulse x-32 ray parametric amplification (IXPA) processes were identified 33 in [14] as decisive for the amplification at the single-atom 34 level.…”
mentioning
confidence: 60%
See 3 more Smart Citations